2021
DOI: 10.1155/2021/6638117
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of 10-Year Survival Outcomes for Early Single Hepatocellular Carcinoma following Different Treatments

Abstract: Introduction. To compare the actual 10-year survival outcomes of early single hepatocellular carcinoma (HCC) patients between 3 first-line treatments: radiofrequency ablation (RFA), surgical resection (SR), or transplantation (LT). Methods. A total of 1255 early single HCC patients retrieved from the Surveillance Epidemiology and End Results (SEER) database were included. Patients survived ≥10 years, and patients died <10 years were compared. Significant predictors associated with 10-year survival were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…A recent Chinese study including 1,255 patients with HCC compared the 10-year survival outcomes from three different first-line treatments, namely, radiofrequency ablation, liver resection, and transplantation. LT was clearly superior in terms of 10-year survival, even after adjustment for confounders and balancing of the compared cohorts using inverse probability weighting ( 8 ). A meta-analysis comparing LT and resection as the treatment options in small HCC meeting the Milan criteria reported that the 5-year OS rates were similar, whereas the 10-year rates were significantly higher in patients who underwent LT than resection (50.0 vs. 29.8%; P < 0.001) ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Chinese study including 1,255 patients with HCC compared the 10-year survival outcomes from three different first-line treatments, namely, radiofrequency ablation, liver resection, and transplantation. LT was clearly superior in terms of 10-year survival, even after adjustment for confounders and balancing of the compared cohorts using inverse probability weighting ( 8 ). A meta-analysis comparing LT and resection as the treatment options in small HCC meeting the Milan criteria reported that the 5-year OS rates were similar, whereas the 10-year rates were significantly higher in patients who underwent LT than resection (50.0 vs. 29.8%; P < 0.001) ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reporting of outcome is usually limited to 5-year survival rates. The impact of LT in the very long follow-up (i.e., ≥10 years) is still an unanswered question, especially when compared to other (curative) approaches such as liver resection ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…For early single HCC, LT is the best treatment. However, since donors are in short supply, both SR and RFA are considered effective treatments [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, over the last two decades, percutaneous ablation with thermal techniques such as radiofrequency ablation (RFA) and microwave ablation (MWA) has emerged as a suitable alternative treatment modality to surgical resection in those with limited dis-ease, particularly those with borderline liver function. Indeed, multiple studies [8][9][10][11][12] have failed to show a significant difference in overall survival between resection and ablation, and results of published meta-analyses comparing the two treatments in BCLC 0, 0/A and A disease have similarly had mixed results, potentially due to poor trial design in many of the primary studies [13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%